1998
DOI: 10.1063/1.476714
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and electron spin resonance studies of the H⋯H, H⋯D, and D⋯D spin-pair radicals in rare gas matrices: A case of extreme singlet–triplet mixing

Abstract: Articles you may be interested inHigh resolution study of spin-orbit mixing and the singlet-triplet gap in chlorocarbene: Stimulated emission pumping spectroscopy of CH 35 Cl and CD 35 Cl Neon and argon matrix ESR and theoretical studies of the 12 CH 3 Cd , 12 CD 3 Cd , 13 CH 3 Cd , 12 CH 3 111 Cd , and 12 CH 3 113 Cd radicalsThe H¯H, H¯D, and D¯D spin-pair radicals have been thoroughly investigated in neon, argon, krypton, and xenon matrices near 4 K by electron spin resonance ͑ESR͒. A theoretical model has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It was found that the g factors and hyperfine interactions of D atoms in the D-D 2 -He solids and in the D-D 2 -Ne-He solids are similar to each other and very close to those obtained for D atoms stabilized in a solid D 2 matrix. 32,37 From the investigation of the saturation behavior of the ESR lines of the D atoms, a relatively short spinlattice relaxation time, T 1 ϭ3ϫ10 Ϫ3 s, was found. All these observations show that D atoms were mainly stabilized inside D 2 clusters.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the g factors and hyperfine interactions of D atoms in the D-D 2 -He solids and in the D-D 2 -Ne-He solids are similar to each other and very close to those obtained for D atoms stabilized in a solid D 2 matrix. 32,37 From the investigation of the saturation behavior of the ESR lines of the D atoms, a relatively short spinlattice relaxation time, T 1 ϭ3ϫ10 Ϫ3 s, was found. All these observations show that D atoms were mainly stabilized inside D 2 clusters.…”
Section: Discussionmentioning
confidence: 99%
“…H • , H 2 +• , and H 4 +• are experimentally known. The isotropic hyperfine coupling constant (iHFCC) of H • in noble gases varies between 501.0 and 512.3 G . Experimental iHFCCs for H 2 +• in various vibrational and rotational states are available. , The value for ν = 0, N = 1 is 329.3 G. Calculations suggest 333.9 G for ν = 0, N = 0 and 334.3 G at an internuclear distance of 1.0584 Å .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Knight et al , [5] who studied by computer modeling the EPR spectra of hydrogen atoms in matrices of noble gases in the range of forbidden transition, discovered the existence of weakly bound hydrogen pairs [5]. The formation of hydrogen pairs, a the peculiar way to deposit atomic hydrogen, was also reported in other media.…”
mentioning
confidence: 95%